WORK IMPROVEMENT OF CUSTOMS AUTHORITIES IN THE CONTEXT OF CREATING A FAVORABLE ENVIRONMENT FOR PEOPLE WITH DISABILITIES: LEGAL ASPECT - Kupriyanova1, Ludmila; Albov, Alexey; Kairova, Alla; Andrianova, Valeria; Nikonovich, Sergey (Revista Inclusiones, 2019)
The article is based on the provisions of modern legal acts regulating legal relations in the customs sphere and determining the need to improve the activities of customs authorities in modern conditions, in which it is important to take into account the growing requirements for the socialization of people with disabilities to organize their social rehabilitation.